Crosstalks between mTORC1 and mTORC2 variagate cytokine signaling to control NK maturation and effector function - Fangjie Wang (Nature Portfolio, 2018)
The metabolic regulator protein family, mTOR, regulate natural killer (NK) cell development and function, but the underlying mechanism is unclear. Here, the authors show that Raptor/mTORC1 and Rictor/mTORC2 form a feedback crosstalk network to variegate cytokine and cellular signaling and modulate NK maturation and effector functions.